End Restraints on Steel Joist Floor Vibrations - Wang, Leon Ru-Liang; Carrle, Gunther (Engineering Journal, 1978)
The problem of perceptible vibrations in steel joist/concrete slab floor systems has been under investigation for nearly 20 years. The vibrations, which can prove to be annoying to occupants, occur as a result of a human footfall. The floors, although structurally safe, lack the flexural rigidity necessary to prevent noticeable oscillations. Two articles by Lenzen6 and Murray, which have presented detailed methods for attacking the vibrations problem, were the primary sources for the background information presented in this paper. The discussion that follows leads to a new method of controlling the floor vibrations problem by varying the rotational end restraints of the floor.